Plastic-Associated Microbial Communities in Aquaculture Areas - Mohsen, Mohamed; Lin, Chenggang; Hamouda, Hamed I.; Al-Zayat, Ahmed M.; Yang, Hongsheng (Frontiers in Marine Science, 2022)
Microorganisms colonize plastics in the aquatic environment but their composition on plastics used in aquaculture remains poorly studied. Microorganisms play a significant role in aquaculture in terms of water quality and the health of cultivated species. In the current study, we explored the composition of microorganisms on floating plastics and their surrounding water collected from ponds and open aquaculture areas. Using scanning electron microscopy, the diversity of microbial communities, primarily diatoms, and bacteria were identified on the plastic surfaces. Additionally, epifluorescence microscopy revealed that prokaryotes were colonized on all plastic samples from 0.1 to 29.27×103 cells/cm2, with a high abundance found in open aquaculture areas compared to ponds. Bacterial communities were characterized by 16S rRNA sequencing which showed that bacterial communities on plastics were dominated by Proteobacteria, Cyanobacteria, Bacteroidetes, and Actinobacteria. The level of these microbial communities on the plastics differed from those found in the surrounding seawater samples and the abundance of potentially pathogenic bacteria was higher in plastics than in seawater samples. Moreover, hydrocarbon-degrading bacteria were more abundant in the investigated plastic samples than in the water samples. This study contributes to the knowledge regarding the plastisphere community in aquaculture.